A laboratory-scale phytocover system for municipal solid waste landfills. Issue 24 (28th October 2022) - Khapre, Abhishek; Khan, Sadaf Aiman; Kumar, Sunil
ABSTRACT: A tremendous increase in municipal solid waste (MSW) generation and its poor management is observed in almost all the developing countries. Landfilling, though undesirable, is an unavoidable disposal option with leachate generation and landfill gas (LFG) emissions as its major inescapable consequences. To evade these dismal outcomes of waste contentment, plant-soil based cover options are being studied widely. In the present study, an attempt was made to employ locally available plants for the phytoremediation of landfills. The experimental set-up was designed using 100 kg of MSW which was laid over with a thin soil layer of 30 cm. The efficiency of the laboratory-scale experimental set-up of 1 m 3 volume was assessed in terms of trace element remediation and LFG oxidation. The initial and final parameters were finally assessed and compared. Plant species were found to develop a strong root zone, thereby reducing the infiltration of water into the waste mass. The present study showed a reduction in LFG emissions of 11.12%, 54.38%, and 32.12% in the deep zone, root zone, and topsoil zone, respectively. Furthermore, the study of the microbes, influencing soil chemical characteristics, could be helpful for designing an appropriate phytocover under diverse climatic conditions of India. GRAPHICAL ABSTRACT: UF0001